Characterization of the aerosol produced from an aerated jet. (1st February 2023) - Succar, Antonella; Lefebvre, Xavier; Prévost, Michèle; Bédard, Emilie; Robert, Etienne
Abstract: Faucet aerators that form aerated water jets generate aerosols, which can constitute a risk of infection if the water is contaminated, particularly for vulnerable individuals near the sink. In this study, we characterize the size and trajectory of water droplets produced from an aerated jet. The detected particle diameter ranged from 3 to 150 μ m . The concentration of droplets in the air varied from near-zero to a maximum of 2 × 1 0 11 particles / m 3, depending on the location relative to the jet. We found four relevant categories of droplets based on their trajectories following their emission at the jet's free surface: particles with inertia high enough to escape the immediate vicinity of the jet (category 1), particles moving towards the jet (category 2), particles drawn into the aerator, which only included particles with a diameter smaller than 50 μ m (category 3), and particles with a near-vertical trajectory (category 4). Tracing category 1 particles to their generation location on the water interface shows a higher emission rate near the aerator. Finally, we employ a numerical model to compute the subsequent trajectories of droplets detected at the limits of the sampled domain. We find that particles whose diameter is smaller than 55 μ m completely dry and become airborne. Larger droplets deposit within a radius of 7 cm around the jet, assuming a surface is located 20 cm below the aerator tip. These results increase the fundamental understanding of the emission mechanisms of droplets in aerated jets and their fate in the sink environment. Highlights: Aerated jets from faucet aerators produce droplets as large as 150 μ m in diameter. Particles are categorized into four groups based on their trajectories. The resulting potential pathogen transmission is either airborne or through fomites. The droplet emission rate decreases downstream of the faucet outlet. A large sink basin and a shield attached to the aerator can limit aerosol spread. Graphical abstract: